Satua Rare Angon Terhadap Pengembangan Bahasa Bali Siswa Kelas VII SMP Sathya Sai Denpasar - Ni Luh Aprianawati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
To enter the realm of language in children, it is very interesting when presented with one. The purpose of this study was to determine how the influence of satua Rare Angon on the development of Balinese language in seventh grade students of SMP Sathya Sai Denpasar, most of the children in this school use Indonesian as a social language in carrying out daily conversations both at school and at school. their respective homes. Through satua Rare Angon, children's vocabulary will increase so that their understanding of these satua increases. So that the results of this study contribute that satua Rare Angon supports the development of the Balinese language in class VII students of SMP Sathya Sai Denpasar.